Oral Valproate Sodium as an Alternative to Benzodiazepine in the Treatment of Catatonia- A Case Report - Maier, Jacob; Rapport, Daniel; McCormick, Alex; Lewis, Chandani (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Alternative therapies are necessary to treat catatonia in patients with comorbidities that are not amenable to therapy with benzodiazepines or ECT. This is a patient with schizophrenia with catatonic features and a history of polysubstance abuse. Consequently, he was not a candidate for treatment with benzodiazepines, so an alternative needed to be found. GABAergic medications have been used previously as alternatives to benzodiazepines and ECT. In this case we chose sodium valproate, due to its cross-reaction with GABAergic systems. There are five reported cases using sodium valproate. Three of which were treated with intravenous valproate, while the remaining two do not specify the route of administration. We present a case where oral sodium valproate was used successfully for both acute and long-term catatonic treatment. To our knowledge, no other report has looked at both acute and long-term treatment with sodium valproate. Oral sodium valproate can be considered for patients with substance use disorders like COPD, sleep apnea or myasthenia gravis in which benzodiazepines are contraindicated and where ECT is not an option for treatment.